Impact of Modern Technology on Undergraduate Students for Teaching and Learning in Tertiary Institutions - Oluwayimika, Kasumu Rebecca; Eberechukwu, Augustine Sandra (American Journal of Creative Education, 2022)
The education sector is becoming more and more reliant on modern technology, which has led to constant communication with students and the availability of many forums for learning support. The study adopted a correlational survey research designed to examine the impact of modern technology on undergraduate students for teaching and learning in tertiary institutions. Three research objectives, three research questions and three hypotheses guided the study. The population of the study is 122 year two students from the department of library and information science, Faculty of Education, Rivers State University and 128 year two students from the department of curriculum studies/instructional technology, Faculty of Education, Ignatius Ajuru University of Education. A sample of 100 students was used for the study. A structured questionnaire was used for the study with a 32 item. Face validity and a reliability coefficient of 0.82 was obtained. Mean and Z test were the statistical tools used for the study. According to the report, modern technology gives teachers and students immediate feedback and enables students to pick up practical life skills. It was suggested that teachers give students a list of places in their school district that offer free internet access (cafés, libraries, restaurants, etc.).